2023
DOI: 10.3389/fonc.2023.1132816
|View full text |Cite
|
Sign up to set email alerts
|

Burden of breast cancer and attributable risk factors in the North Africa and Middle East region, 1990–2019: a systematic analysis for the Global Burden of Disease Study 2019

Abstract: BackgroundBreast cancer (BC) is the most common cancer in women globally. The North Africa and Middle East (NAME) region is coping hard with the burden of BC. We aimed to present the latest epidemiology of BC and its risk factors in this region.MethodsWe retrieved the data on BC burden and risk factors from the Global Burden of Disease Study 2019 to describe BC status in the 21 countries of the NAME region from 1990 to 2019. We explored BC incidence, prevalence, deaths, disability-adjusted life years (DALYs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…By analysing data from the past 30 years, we determined the global burden of thyroid cancer and predicted its trends over the next decade [ 43 ]. We found that the burden of thyroid cancer is on the rise globally, especially among women aged ≥80 years and in low- and medium-SDI regions, suggesting a need for targeted, effective prevention, diagnosis, and treatment of thyroid cancer, as well as for personalised medical and public health strategies for these populations and regions [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…By analysing data from the past 30 years, we determined the global burden of thyroid cancer and predicted its trends over the next decade [ 43 ]. We found that the burden of thyroid cancer is on the rise globally, especially among women aged ≥80 years and in low- and medium-SDI regions, suggesting a need for targeted, effective prevention, diagnosis, and treatment of thyroid cancer, as well as for personalised medical and public health strategies for these populations and regions [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…While PD-L1 expression level is thought to be a good predictive marker for RR or treatment [100] , Taube et al have introduced the idea that although PD-L1 expression can be a good predictive marker, it can be a sign of immunogenic tumor and probably more aggressive ones [39,101] . Only one side effect of therapy using anit-PD-1/PD-L1 antibodies has been mentioned so far, but it is righteous to hint at numerous clinical studies that work on the side effects of these drugs and have reported different cases, from colitis to myocarditis [102] .…”
Section: Melanomamentioning
confidence: 99%
“…Despite substantial efforts have been dedicated to exploring changes in BC mortality over time and age-specific mortality ( 13 , 14 ) and investigating various associated risk factors ( 15 18 ), there is a lack of comprehensive analysis on the specific impact of MRs on BC mortality in Chinese women in terms of time trends and cohort effects. In this study, we analyzed pertinent data from GBD 2019, employing an age-period-cohort (APC) model ( 19 ) to delineate the temporal trends of BC mortality attributed to MRs (HFPG and HBMI).…”
Section: Introductionmentioning
confidence: 99%